Ḥaṭṭûr šelöši la’alîlôt hā'ēlîm. paršegēn kol šîrôt 'ûgārît - Rin, S. (1979)
The Third Column of the Acts of the Gods. A Hebrew Paraphrase of the Ugaritic Epic Poetry; For orders write to Inbal, Box 42, Narberth, Pa. 19072; 1-75: Baal and Anat; 76-78: Birth of the Gracious Gods; 79-80: Wedding of Nikkal and ‘Ib; 81-108: Keret; 109-133: Aqht.